Urinothorax in a patient with lung cancer and a second primary tumor - Francisco Martínez Feria; Aurora López García (Centro Provincial de Información de Ciencias Médicas, 2019)
The case report of a 51 years patient with a history of neoplasm in the right lung is described, for which she received treatment with chemotherapy. Approximately 3 years later she began to present colic type pain in left flank and lumbar cavity accompanied by fall of the urinary volume, reason why she was assisted in Dr. Juan Bruno Zayas Alfonso Teaching General Hospital inSantiago de Cubawhere she was diagnosed cervical cancer, stage IIIB. Left percutaneous nephrostomy was made and the level of pleural effusion disappeared within a week. The patient was discharged with appropriate diuresis and normal figures of creatinine; later on radiotherapy was indicated against the gynecological cancer.